2019
DOI: 10.1242/bio.046961
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of copper-trafficking chaperones causes gene-specific systemic pathology inDrosophila melanogaster: prospective expansion of mutational landscapes that regulate tumor resistance to cisplatin

Abstract: Copper, a transition metal, is an essential component for normal growth and development. It acts as a critical co-factor of many enzymes that play key roles in diverse cellular processes. The present study attempts to investigate the regulatory functions decisively controlling copper trafficking during development and aging of the Drosophila model system. Hence, through engagement of the GAL4/UAS genetic platform and RNAi technology, we herein examined the in vivo significance of Atox1 and CCS genes, products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Unfortunately, all flies used in this study were disposed of during the Covid-19 contingency and we cannot, regretfully, revisit this issue on the same set of flies. With these considerations in mind, and given the known requirement of copper for pigmentation (Binks et al 2010 ; Turski and Thiele 2007 ; Zhang et al 2020 ; Zhou et al 2003 ), in addition to other physiological processes (Comstra et al 2017 ; Kirby et al 2008 ; Sellami et al 2012 ; Theotoki et al 2019 ; Wang et al 2018 ), we conclude this report suggesting that the observed correlation between copper content and pigmentation in D. melanogaster could be explained by an increased requirement for tyrosinase activity for melanin production in this species. To further test this hypothesis, an unambiguous identification of the copper-dependent enzyme involved in epidermal pigment melanization would be helpful (Riedel et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, all flies used in this study were disposed of during the Covid-19 contingency and we cannot, regretfully, revisit this issue on the same set of flies. With these considerations in mind, and given the known requirement of copper for pigmentation (Binks et al 2010 ; Turski and Thiele 2007 ; Zhang et al 2020 ; Zhou et al 2003 ), in addition to other physiological processes (Comstra et al 2017 ; Kirby et al 2008 ; Sellami et al 2012 ; Theotoki et al 2019 ; Wang et al 2018 ), we conclude this report suggesting that the observed correlation between copper content and pigmentation in D. melanogaster could be explained by an increased requirement for tyrosinase activity for melanin production in this species. To further test this hypothesis, an unambiguous identification of the copper-dependent enzyme involved in epidermal pigment melanization would be helpful (Riedel et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Cu ions can also be transported by copper chaperone (CCS) to SOD1 along a pathway conserved from flies to mammals. Cu can then act as a metal cofactor for SOD1 [ 97 , 98 ]. Transfections of human CCS and human Ctr1 have rescued fly survival on toxic Cu conditions [ 97 ], suggesting that either protein can support SOD1 function, allowing the fly to combat the resulting oxidative stress from the Cu toxic conditions.…”
Section: Metal Transport Systems In Drosophila Melanogastermentioning
confidence: 99%
“…cDDP can also bind Cox17 at (Cys26 and Cys27) [33]. Moreover, in a fruit fly model, it was found that cDDP can bind CCS [34], also to the conserved 12 CXX 15 C-Cu(I) binding motif [35], supporting that cDDP and Cu(I) share similar mechanisms in intracellular trafficking (Figure 1).…”
Section: Cu Chaperones In Intracellular Cddp Traffickingmentioning
confidence: 76%